Analyses of K-12 human trafficking awareness and prevention education (HTAPE) curricula for elements of cultural responsiveness, trauma-informed care, and ecofeminist principles - Bissonnette, Brooke, author; Basile, Vincent, advisor; Jennings, Louise, committee member; Albert, Lumina, committee member; Gonzalez-Voller, Jessica, committee member (Colorado State University. Libraries, 2025)
This dissertation investigates human trafficking awareness and prevention education (HTAPE) for youth in Denver and Aurora, Colorado, where cultural and trauma-related factors increase vulnerability. Using ecofeminism to frame systemic causes, culturally responsive teaching to assess educational relevance, and trauma-informed care to guide practice, the study critiques existing HTAPE curricula. Findings indicate limited attention to trauma manifestations, cultural contexts, and teacher preparedness. Recommendations call for integrating these theoretical frameworks to design comprehensive and equitable curricula that empower educators, promote resilience, and more effectively protect youth from exploitation.
Keywords: culturally responsive teaching; human trafficking; trauma informed care; ecofeminism; awareness education; prevention education